Dosimetric Accuracy of MR-Guided Online Adaptive Planning for Nasopharyngeal Carcinoma Radiotherapy on 1.5 T MR-Linac - Ding, Shouliang; Liu, Hongdong; Li, Yongbao; Wang, Bin; Li, Rui; Huang, Xiaoyan (Frontiers in Oncology, 2022)
Purpose: To evaluate the dose accuracy of bulk relative electron density (rED) approach for application in 1.5 T MR-Linac, and assess the reliability of this approach in the case of online adaptive MR-guided radiotherapy for Nasopharyngeal Carcinoma (NPC) patients. Methods: Ten NPC patients formerly treated on conventional linac were included in this study, with their original planning CT and MRI collected. For each patient, structures such as the targets, organs at risk, bone and air regions were delineated on original CT in Monaco system (v5.40.02). To simulate the online adaptive workflow, firstly all contours were transferred to MRI from original CT using rigid registration in Monaco system. Based on the structures, three different types of synthetic CT (sCT) were generated from MRI using bulk rED assignment approach: the sCTICRU uses the rED values recommended by ICRU46, the sCTtailor uses the patient-specific mean rED values, and the sCTHomogeneity uses homogeneous water equivalent value. The same treatment plan was calculated on three sCTs and original CT. Dose calculation accuracy was investigated in terms of gamma analysis, point dose comparison and dose volume histogram (DVH) parameters. Results: Good agreement of dose distribution was observed between sCTtailor and original CT, with gamma passing rate (3%/3mm) of 97.81% ± 1.06%, higher than that of sCTICRU (94.27% ± 1.48%, p = 0.005) and sCTHomogeneity (96.50% ± 1.02%, p = 0.005). For stricter criteria 1%/1mm, gamma passing rate for plans on sCTtailor, sCTICRU and sCTHomogeneity were 86.79% ± 4.31%, 79.81% ± 3.63% and 77.56% ± 4.64%, respectively. The mean point dose difference in PTVnx between sCTtailor and planning CT was -0.14% ± 1.44%, much lower than that calculated on sCTICRU (-8.77% ± 2.33%) and sCTHomogeneity (1.65% ± 2.57%), all with p < 0.05. The DVH differences for plan based on sCTtailor were much smaller than sCTICRU and sCTHomogeneity. Conclusions: The bulk rED assigned sCT by adopting the patient-specific rED values can achieve a clinically acceptable level of dose calculation accuracy in the presence of 1.5 T magnetic field, making it suitable for online adaptive MR-guided radiotherapy for NPC patients.